2016
DOI: 10.3390/vaccines4020018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion: A Promising Target for Nanoparticle-Based Vaccine Delivery Systems

Abstract: Vaccination is one of the most popular technologies in disease prevention and eradication. It is promising to improve immunization efficiency by using vectors and/or adjuvant delivery systems. Nanoparticle (NP)-based delivery systems have attracted increasing interest due to enhancement of antigen uptake via prevention of vaccine degradation in the biological environment and the intrinsic immune-stimulatory properties of the materials. Mitochondria play paramount roles in cell life and death and are promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…In addition to increase of ROS production, more interestingly, photodynamically induced mitochondrial apoptosis induces signal transduction pathways, which also participate in the development of immune responses [ 86 ]. Marrache et al reported their study regarding the use of mitochondria-targeted-nanoparticle delivery systems to deliver mitochondria-acting photosensitizer for generation of tumor cell antigens to activate DCs ex vivo for potential immune response.…”
Section: Future Perspectives Of Improving Anticancer Immune Responmentioning
confidence: 99%
“…In addition to increase of ROS production, more interestingly, photodynamically induced mitochondrial apoptosis induces signal transduction pathways, which also participate in the development of immune responses [ 86 ]. Marrache et al reported their study regarding the use of mitochondria-targeted-nanoparticle delivery systems to deliver mitochondria-acting photosensitizer for generation of tumor cell antigens to activate DCs ex vivo for potential immune response.…”
Section: Future Perspectives Of Improving Anticancer Immune Responmentioning
confidence: 99%
“…Various types of nanoparticles can be used as delivery systems or as adjuvants, such as polymeric nanoparticles, liposomes, micelles, carbon nanotubes, mesoporous silica nanoparticles (MSNs), gold nanoparticles (AuNPs), virus nanoparticles, acting alone or in combination ( Figure 1) [28]. Adding specific surface targeting moieties can significantly enhance delivery and hone nanoparticles to specific subcellular organelles involved in immune response [29][30][31][32][33]. Active vaccine systems can be formulated by incorporating cell-penetrating peptides, APC-specific cellular epitopes or immune-stimulant lipid moieties [34].…”
Section: Nanoparticles As Vaccine Delivery Systemsmentioning
confidence: 99%
“…To achieve mitochondrial‐targeting drug delivery, various nanoparticles are decorated with targeting ligands, especially triphenylphosphonium (TPP), which has the advantages of simple purification and modification. [ 24 ] Molecules are easily and precisely accumulated in the mitochondrial matrix through the lipid bilayer on account of their lipophilic and hydrophilic properties with TPP modification. [ 25 ] Therefore, an excellent mitochondrial‐targeting nanoparticle should be silent in blood circulation or normal tissues and activated once entering tumors.…”
Section: Introductionmentioning
confidence: 99%